The New Orleans murder epidemic: Emmanuel Levinas and Jacques Derrida on the irresponsibility of violence - Zimmer, Jacqueline Nicole (2014)
Corruption, unfettered violence, and racist enforcement tactics have historically defined the operations of the New Orleans Police Department, and consequently, many New Orleanians do not expect to be helped or protected by law enforcement or the justice system. The breakdown of society’s civil code explains why many New Orleans citizens have normalized the use of coercive violence to solve interpersonal disputes instead of relying on legitimate policing methods to maintain social order. In the past year, the city of New Orleans has implemented criminologist David Kennedy’s Group Violence Reduction Strategy (GVRS), which aims to decrease the city’s historically high murder rate. This essay investigates the relationship between Emmanuel Lévinas’ and Jacques Derrida’s conception of responsibility to the other and hospitality and New Orleans’ culture of violence, and how the endemic lack of trust in New Orleans’ Police Department compromises the ethical imperative Lévinas conceives of as implicit in every encounter with the other. The violent reception of the other is the denial of the infinite otherness of the other and is influenced by contextual conditions, such as poverty and high gun ownership rates that cultivate an environment of fear and heighten one’s perceived risk of being victimized. Specifically, this study examines the effect that the breakdown in a city’s civil code has on one’s experience of the face-to-face encounter with the other, and how this breakdown has led to the reliance on various means of vigilante justice as a normative method of conflict resolution. This essay examines current political, legal, and judicial attempts being made to combat the murder epidemic, and argues that while some of these attempts fall short because they fail to address prevailing community norms that tolerate and encourage violence as a means to right wrongs, a strategy that is rooted in hospitality has the potential to be effective in the long run. Lévinas and Derrida, when read in dialogue with each other, offer us an ethical framework for analyzing the conditions that inform the irresponsible decision to do violence to the other and strategies that aim to ‘fix’ a city’s violence problem